Supervisor knowledge and clinical supervision effects on teacher performance - Hazizul, Hazizul; Radiana, Usman; Karolina, Venny; Asrori , Asrori; Waruwu, Marinu (Indonesian Research Journal in Education |IRJE|, 2026)
This study examines the influence of supervisor knowledge and clinical supervision on teacher performance in senior high schools in Kapuas Hulu Regency, Indonesia. A quantitative survey design was employed involving 209 teachers selected through purposive sampling from a population of 557 teachers across 32 schools. Data were collected using Likert-scale questionnaires measuring supervisor knowledge and clinical supervision, while teacher performance data were obtained from teacher performance management assessments. The collected data were analyzed using descriptive statistics, simple linear regression, and multiple regression with SPSS. The results indicate that supervisor knowledge significantly influences teacher performance with a coefficient of determination of 67.5%. Clinical supervision also has a significant effect on teacher performance, accounting for 74.6%. When analyzed simultaneously, supervisor knowledge and clinical supervision account for 77.6% of teacher performance improvement. These findings highlight the importance of strengthening supervisors’ professional knowledge and implementing systematic clinical supervision to enhance teacher performance and improve the overall quality of education.